1992
DOI: 10.1007/bf01187119
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the sprouting response of axon-like processes from retinal ganglion cells after axotomy in adult hamsters: a model using intravitreal implantation of a peripheral nerve

Abstract: Peripheral nerves provide a favourable environment for damaged CNS axons to sprout and regenerate. It has also been demonstrated that retinal ganglion cells respond to a peripheral nerve segment grafted to the retina by emitting axon-like processes from the somatodendritic compartment into the graft. The factors influencing the pattern of sprouting of axotomized retinal ganglion cells were explored in this study by implanting a short segment of peripheral nerve, which did not come into contact with the retina,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…In addition, SCs are known to release soluble factors that can induce sprouting and increase regeneration of some neurons independent of contact with SCcontaining PN grafts (Cho and So, 1992;Berry et al, 1996). The lack of CST regeneration observed under these conditions is consistent with several other published retrograde tracing studies which failed to demonstrate labelling of cortical motor neurons from thoracically placed SC or PN grafts in transection sites (Richardson et al, 1980(Richardson et al, , 1984Xu et al, 1995a,b;Chen et al, 1996;Menei et al, 1996).…”
Section: Axonal Die-back and Lack Of Cst Sprouting Response To Graftssupporting
confidence: 80%
“…In addition, SCs are known to release soluble factors that can induce sprouting and increase regeneration of some neurons independent of contact with SCcontaining PN grafts (Cho and So, 1992;Berry et al, 1996). The lack of CST regeneration observed under these conditions is consistent with several other published retrograde tracing studies which failed to demonstrate labelling of cortical motor neurons from thoracically placed SC or PN grafts in transection sites (Richardson et al, 1980(Richardson et al, , 1984Xu et al, 1995a,b;Chen et al, 1996;Menei et al, 1996).…”
Section: Axonal Die-back and Lack Of Cst Sprouting Response To Graftssupporting
confidence: 80%
“…3(A) in Watanabe et al, 19911. Thick, axon-like processes in the nerve fiber layer were also observed, as in rat (Thanos, 1988;Tabata and Fukuda, 1992), hamster (Cho and So, 1992), and cat (Watanabe et al, 1993b) RGCs with regenerated axons. The morphological changes observed in RGCs with regenerated axons probably resulted from the ON transection.…”
Section: Morphological Changes Of Surviving Rgcsmentioning
confidence: 88%
“…Such injury results in the accumulation of axonally transported asyn, APP, PrP and in some cases tau at the proximal axon stump of injured neurons that are reminiscent of axonal swellings containing these proteins in AANDs (15,162,212). Studies in lower vertebrate (98,99,101) and mammalian (45,144,182) systems have consistently suggested that polarity loss induced by proximal axotomy could be a mechanism capable of linking axonal injury and the development of AAND-like neuropathology. Proximal axotomy induces ectopic axonlike sprouting (98,182), the aberrant phosphorylation and missorting of cytoskeletal proteins (99, 100) and thus reproduces key aspects of AD neuritic pathology (26,107,174).…”
Section: Is Polarity Loss Connected To the Misprocessing And Secretiomentioning
confidence: 99%